Acute Treatment Patterns for Lower Extremity Trauma in the United States: Flaps versus Amputation - Mundy, Lily R.; Truong, Tracy; Shammas, Ronnie L.; Gage, Mark J.; Pomann, Gina-Maria; Hollenbeck, Scott T. (Journal of Reconstructive Microsurgery, 2017)
Background Treatment algorithms for large soft tissue defects in lower extremity trauma are not clearly defined. The aim of this study is to determine if there are geographic or demographic differences in the management of open tibia fractures with soft tissue defects requiring either soft tissue reconstruction or amputation in the United States (US). Methods A retrospective analysis was performed on the Nationwide Inpatient Sample (NIS), 2000 to 2011. We evaluated flap and amputation rates in the open tibia fractures with soft tissue defects based on geographic and socioeconomic factors. Results From 2000 to 2011, there were 175,283 open tibia fractures in the US; 7.2% (n = 12,620) had a concomitant soft tissue defect requiring either flap or amputation. The overall flap rate was 73.2% (n = 9,235). When compared with the South at 68%, flap rates were highest in the West at 79% (adjusted odds ratio [AOR] = 2.06; 95% confidence interval [CI] = 1.49, 2.86; p < 0.0001), followed by the Northeast at 77% (AOR = 1.63; 95% CI = 1.22, 2.19; p = 0.001), and the Midwest at 74% (AOR = 1.76; 95% CI = 1.25, 2.47; p = 0.001). Flap rates were lower in the rural hospitals in the West (AOR = 0.24; 95% CI = 0.07, 0.84; p = 0.03) and Northeast (AOR = 0.55; 95% CI = 0.37, 0.82; p = 0.003) when compared with the urban hospitals. Flap rates were highest in the highest income quartile at 77% (AOR = 1.53; 95% CI = 1.05, 2.25; p = 0.03) compared with 72% in the lowest income quartile.Conclusions Reconstruction rates were significantly higher in three major US regions when compared with the South, urban hospitals in the West and Northeast, and the highest income quartile.
Keywords: lower extremity trauma; flap; soft tissue reconstruction; open tibia fracture